Rise Up - Evans, Lisa (Oberon Books, 2015)
The tide was turning - though local governments disagreed, it would soon be illegal to segregate black Americans from white Americans on public buses, in waiting rooms or in restaurants. And yet - in the early 1960s, many states across the south of America kept discriminating against African Americans ... In modern day Britain, four performers tell the stories of the Freedom Riders - principled citizens riding buses across Alabama and Mississippi, drawing attention to this illegal discrimination and facing up to terrifying violence with peaceful resistance. The story of the Freedom Riders is one of ordinary people becoming a civil rights movement, taking on the establishment and changing the world. In a time of Michael Brown, Trayvon Martin and Mark Duggan, what does it mean for people to come together and rise up?